Analisis Pengaruh Pendapatan Terhadap Konsumsi Mahasiswa FEBI UIN Sultan Maulana Hsanuddin Banten (Jurnal Kendali Akuntansi, 2023)
This study aims to examine and analyze the effect of income on consumption patterns of students of the Faculty of Islamic Economics and Business at UIN Sultan Maulana Hasanuddin Banten and to determine differences in consumption patterns of FEBI students at UIN BANTEN based on scholarship recipients, gender and place of residence. This study used a quantitative approach by distributing questionnaires to 30 respondents. Then the collected data were analyzed using a simple regression equation with the help of the Eviews program and the average difference test with the help of the SPSS program. The results of the simple linear regression equation obtained Y = 1.850 + 0.680X a constant of 1.850 which is the value of consumption before it is affected by income, then the regression coefficient equal to 0.680 is the value of income which has a positive and significant influence on the level of student consumption and if increased Rp. 100,000 it will increase consumption by Rp. 68,000. Then it can be seen that the coefficient of determination is 0.345 or when multiplied by 100 percent, 34.5% of the income variable will influence the level of consumption of FEBI students at UIN Banten in Serang City and the remaining 65.5% is influenced by other variables not included in the study This. The variable is additional income. The t test obtained t count > t table or obtained 3.840 > t table 2.048 thus Ho was rejected and Ha was accepted so that it can be stated that income has a positive and significant effect on the level of consumption of FEBI Banten UIN students in Serang City.